Functional and Genomic Characterization of a Pseudomonas aeruginosa Strain Isolated From the Southwestern Gulf of Mexico Reveals an Enhanced Adaptation for Long-Chain Alkane Degradation - Muriel-Millán, Luis Felipe; Rodríguez-Mejía, José Luis; Godoy-Lozano, Elizabeth Ernestina; Rivera-Gómez, Nancy; Gutierrez-Rios, Rosa-María; Morales-Guzmán, Daniel; Trejo-Hernández, María R.; Estradas-Romero, Alejandro; Pardo-López, Liliana (Frontiers in Marine Science, 2019)
Indigenous bacterial populations play an important role in the restoration of crude oil-polluted marine environments. The identification and characterization of these bacteria are key in defining bioremediation strategies for the mitigation of possible future oil spills. In this work, we characterized Pseudomonas aeruginosa strain GOM1, which was isolated from the water column in the southwestern Gulf of Mexico. Phylogenetic analysis revealed that GOM1 strain was most closely related to P. aeruginosa WC55, a strain isolated from the northern Gulf of Mexico after the Deepwater Horizon oil spill. The hydrocarbon-degrading capacity of P. aeruginosa GOM1 was investigated using various approaches. This strain degraded 96% of the aliphatic fraction (C12-C38) of crude oil during a 30-day incubation period, exhibiting a high activity on long-chain alkanes, and expressing alkane hydroxylases AlkB1, AlkB2 and AlmA. Addition of nitrogen and phosphate to seawater culture medium enhanced hexadecane degradation by GOM1. Additionally, the strain exhibited high surfactant/rhamnolipid production and emulsifying activity when grown in a complex medium in the presence of hexadecane. Comparisons of growth kinetics, hydrocarbon degradation and gene expression between GOM1 and the closely related P. aeruginosa laboratory strain PAO1 revealed that the marine isolate is better adapted to degrade alkanes. Taken together, our results place P. aeruginosa GOM1 as a potentially effective candidate to be included in a consortium for use in the bioremediation of oil-polluted sites.